The effect of using internal and external feedback in learning some volleyball skills (Journal of the College of Basic Education, 2022)
The aim of the research is to identify the effect of feedback of all kinds, internal and external, on learning some volleyball skills, and to discover the best type that helps to learn skills.With the experimental groups, the researcher used the visual feedback method via video and illustrative images, in addition to the verbal explanation method, and the performance of the model in the internal (individual) feedback and the collective (external) feedback, while with the control group, she used the feedback method by verbal explanation and model performance only.